Mode of admission and its effect on adherence to reperfusion therapy guidelines in Belgian STEMI patients. Issue 5 (September 2016) - Rousseaux, Céline; Mols, Pierre; Sinnaeve, Peter R; Convens, Carl; Dubois, Philippe; Vranckx, Pascal; Gevaert, Sofie; Coussement, Patrick; Ramadan, Ahmed SE; Beauloye, Christophe; Renard, Marc; Evrard, Patrick; et al.
Objectives: Emergency medical services play a key role in the recognition and treatment of ST-segment elevation myocardial infarction (STEMI). This study evaluates the effect of emergency medical services use on adherence to reperfusion therapy guidelines in Belgian STEMI patients and on in-hospital mortality. Methods: The mode of admission with against without emergency medical services was associated with baseline risk profile, reperfusion modalities and in-hospital mortality in 5692 consecutive STEMI patients from 2012 to 2014. Results: A total of 3896 STEMI patients (68%) were transported to the hospital by emergency medical services, and 1796 patients (32%) arrived at the hospital using their own transport (self-referral). Emergency medical services patients were older than self-referral patients (64 vs. 62 years) and more frequently presented with cardiac arrest (14% vs. 5%) and with cardiogenic shock (10% vs. 4%). Emergency medical services patients received primary percutaneous coronary intervention more often (95% vs. 91%, P <0.0001) and more frequently within 90 minutes (72% vs. 65%, P <0.001). Moreover, the time interval between symptom onset and reperfusion therapy was shorter in the emergency medical services group (median of 195 vs. 255 minutes, P <0.001). Crude in-hospital mortality was higher in the emergency medical services group (7.7% vs. 3.8%, P <0.0001) and was mainly driven by the high prevalence of cardiogenic shock and cardiac arrest in the emergency medical services group. After adjustment, the impact on mortality was no longer significantly different. Conclusion: Emergency medical services are used by two-thirds of Belgian STEMI patients and are associated with a better adherence to STEMI reperfusion guidelines. These data favour the use of emergency medical services as the preferred transfer system for patients with chest pain suspicious for STEMI.